Alternatives for scientific dissemination in universities - Mabel Rodríguez Moya; Yuleydi Alcaide Guardado; César David Fuentes Rodríguez (Medisur)
Scientific dissemination involves activities development that interpret and make scientific knowledge accessible to society; it includes all those tasks that carry out scientific knowledge to people interested in understanding or becoming informed about a certain area of knowledge. The purpose of this research is to systematize knowledge about scientific dissemination and its importance in universities. A search was carried out in the SciELO, Redalyc and Dialnet databases, using the Google Scholar search engine. Keywords combinations of “scientific dissemination, university, “academic social networks” were applied. Based on the obtained information, a bibliographic review of 163 documents was carried out; Those that did not adequately address the topics of interest were excluded, and 27 were selected. University management of scientific dissemination has a very promising future to contribute to sustainable development, as long as its appropriate conception and implementation is achieved. In the academic sphere, it is necessary not only to be a good researcher, but also to generate management and knowledge transfer processes. It is concluded that the university constitutes one of the institutions that can contribute the most to the dissemination of science, and to achieve this it is vital that university professors in their role as researchers develop skills for socializing their researches’ results.